Protecting Schools and Hospitals from Natural Hazards - Ferrucci, Matteo (World Bank, Washington, DC, 2012)
Evidence from past events in the East Asia and Pacific Region demonstrates that such critical infrastructure as health and educational facilities is heavily exposed to natural disasters. In Myanmar in 2008, Cyclone Nargis damaged or destroyed nearly 75 percent of the health facilities and more than half schools in the area affected3. Super Typhoon Durian hit the Philippines in 2006 and damaged more than half of the schools in five different cities, costing US$20 million. In this scenario, there is a growing necessity of preventing natural hazards from having such a devastating impact on critical infrastructure. Enhancing the resilience of schools and hospitals to natural disasters is a responsibility of all authorities and stakeholders involved and a priority for the Disaster Risk Management (DRM) agenda. Not only would lives and property be saved, but more effective emergency management will be enabled. In fact, schools and hospitals can serve as community shelters during a disaster or as a place to coordinate post disaster activities. Considering the critical role of schools and hospitals, priority should be placed on identifying and reducing the weaknesses of existing facilities and on improving the building standards for new construction. While damage and losses associated with extreme events may exceed a country's gross domestic product (GDP), the implementation of mitigation measures aimed at improving the resilience of existing facilities provides a cost-effective preventive solution, generally limited to 4 percent of the initial investment cost.